Experiences of Elementary School Teachers in Handling Learners with Special Needs - Tabiado, Danica; Siay, Meraflor P.; Unabia, Mary Dianne; Dela Rama, Junmar; Valmorida, Francis May S. (SITTAH: Journal of Primary Education, 2025)
This qualitative study focuses on elementary teachers' experiences in handling learners with special needs, where teachers encountered different types of learners with special needs, their preparations in handling them, accommodations, time allocation, challenges, and ways of coping with them. Using the Meriam 1998 model, interviews were conducted with seven elementary teachers, one principal, and two selected parents to gain insights into their experiences. This study utilized the social learning theory by Albert Bandura, which emphasizes the importance of observational learning. Findings reveal that the teachers encountered different types of learners with special needs: global developmental delay, autism, and selective mutism. Their ways of preparing them are identifying the needs of the learners, preparing specialized activities, and attending seminars and training. They work to create a positive learning environment, provide additional attention, and incorporate differentiated instruction to accommodate learners with special needs. Teachers also manage their time by adjusting time schedules and time blocking accordingly. Despite their preparations, teachers often need help due to their time, learners' short attention spans, and inadequate teacher training. However, they can cope with prioritizing time management, making individualized educational plans (IEPs), and engaging in reflection and further research. Based on the findings, recommendations provide continuous support and resources, such as teaching guides, that will be available to deliver adequate educational support to learners with special needs.